Understanding an Extension Technology Acceptance Model of Google Translation: A Multi-Cultural Study in United Arab Emirates - Saeed Al-Maroof, Rana (2020)
The importance of using Google Translate (GT) has become dominantly more effective. Most researchers, professors, and students rely on its translation as an immediate source of getting information in different coun tries all over the world. However, previous studies failed to cover these influen tial factors that pinpoint the relation between GT and user's intention, and con sequently fail to discover the effects of using GT. The purpose of this study is to explore GT acceptance in United Arab Emirates (UAE). It is assumed that us ers' attitude towards GT may vary based on the language used. The variations in languages are unidirectional where at least two languages are involved in this process. The suggested analytical framework is based on an extended TAM model. A quantitative methodology approach was adopted in this study. The hypothesized model is validated empirically using the responses received from a survey of 368 respondents, which were analyzed using structural equation modeling (SEM-PLS). Results indicated that Perceived Ease of Use, Perceived Usefulness, and Motivation have a significant impact on Behavioral Intention to use GT. In addition, Perceived Usefulness and Motivation significantly influ enced Perceived Ease of Use. Furthermore, Perceived Usefulness is in turn in fluenced by Experience. The findings provide significant theoretical and practi cal implications for translation researchers, teachers, and machine translation system developers.